Makna Prosesi Dan Nilai Pendidikan Karakter Dalam Tradisi Lomban Kupatan Tayu (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2024)
This research aims to (1) describe the meaning of the Tayu Lombang Kupatan tradition procession and (2) identify the character education values ​​contained in the Tayu Lombang Kupatan tradition. This research was conducted in Sambiroto Village, Tayu District, Pati Regency, and at SMAN 2 Pati, located at Jl. A. Yani No.4, Winong, Pati District, Pati Regency. This research uses a qualitative descriptive method with Roland Barthes' semiotic approach. The data in this research are the processions and ubarampe in the Tayu race of Lemban Kupatan. The data sources in this research are the events of the implementation of the Limban Kupatan Tayu tradition, informants, and documents. The sampling technique in this research is purposive sampling. This research uses data collection techniques through interviews and document analysis. Test the validity of the data in this research using source and theory triangulation. Data analysis in this research uses data analysis techniques, according to Milles and Huberman. The results of this research show that the traditional Lomban Kupatan Tayu processions have connotative meanings. Likewise, in the ubarampe, the buffalo head is a symbol of the sub-district head and its residents, the goat head is a symbol of the village head and his residents, yellow rice is a symbol of gold, coconut leaves is a symbol of glory, banana leaves as a symbol of the strength of heart, ketupat as a symbol of mistakes, lepet as a symbol of close community relations, barong as a symbol of guidance, ingkung chicken. A symbol of the power of prayer, nasi uduk is a symbol of pleasure, and plantains symbolize gold. The character education values ​​contained in the Lombang Kupatan Tayu tradition are the principles of respect, the principle of harmony, the character of being wise, honest, self-aware, alert, forming excellent and correct morals and etiquette, and the moral of being careful. The results of this research are also relevant as teaching material for class, mainly expository texts.